Konstruksi Orientasi Politik Siswa SMA di Kabupaten Sleman - Mirza Hardian (Jurnal Rontal Keilmuan Pancasila dan Kewarganegaraan, 2021)
Family and school are the agents of political socialization that play a major role in shaping the political orientation of students. Both of them have enormous control because most of the process in transmitting information about politics takes place in the family and school environment which has an impact on the formation of political orientation. This study aims to determine the role of families and schools in the formation of students' political orientation in Sleman Regency. The approach to this research is quantitative with a survey method to the 307 people who were randomly selected as sample of this research. The result show that the role of family and school was still low. In this case, the role of the family in the formation of political orientation by 31%, while the role of the school made an effective contribution of 5.3%.